Directing Charge Transfer in a Chemical‐Bonded BaTiO3@ReS2 Schottky Heterojunction for Piezoelectric Enhanced Photocatalysis. Issue 29 (7th June 2022) - Liu, Wei; Wang, Peifang; Ao, Yanhui; Chen, Juan; Gao, Xin; Jia, Baohua; Ma, Tianyi
Abstract: The piezo‐assisted photocatalysis system, which can utilize solar energy and mechanical energy simulteneously, is promising but still challenging in the environmental remediation field. In this work, a novel metal–semiconductor BaTiO3 @ReS2 Schottky heterostructure is designed and it shows high‐efficiency on piezo‐assisted photocatalytic molecular oxygen activation. By combining experiment and calculation results, the distorted metal‐phase ReS2 nanosheets are found to be closely anchored on the surface of the BaTiO3 nanorods, through interfacial ReO covalent bonds. The Schottky heterostructure not only forms electron‐transfer channels but also exhibits enhanced oxygen activation capacity, which are helpful to produce more superoxide radicals. The polarization field induced by the piezoelectric BaTiO3 can lower the Schottky barrier and thus reduce the transfer resistance of photogenerated electrons directing to the ReS2 . As a result of the synergy effect between the two components, the BaTiO3 @ReS2 exhibits untrahigh activity for degradation of pollutants with an apparent rate constant of 0.133 min −1 for piezo‐assisted photocatalysis, which is 16.6 and 2.44 times as that of piezocatalysis and photocatalysis, respectively. This performance is higher than most reported BaTiO3 ‐based piezo‐assisted photocatalysis systems. This work paves the way for the design of high‐efficiency piezo‐assisted photocatalytic materials for environmental remediation through using green energies in nature. Abstract : The BaTiO3 @ReS2 piezo‐assisted photocatalysis system with interfacial ReO covalent bond exhibits excellent synergy between piezoelectric and photocatalytic. The polarization field induced by the piezoelectric response can lower the Schottky barrier and thus reduce the transfer resistance of photogenerated electrons. The interfacial ReO covalent bond ensures the formation of a seamless contact interface and acts as the "bridge" for the electron transfer.